Uranium analysis by neutron induced fissionography method using solid state nuclear track detectors - Tretyakova, S. P.; Güzel, T.; AKYÜZ, SEVİM; AKYÜZ, ZEKİ TANIL (Elsevier, 1999)
In this study total twenty samples (eight reference materials and twelve sediment samples) were analysed for their uranium content which is in the range of 1–17 μg/g, by neutron induced fissionography (NIF) method using solid state nuclear track detectors (SSNTDs) in comparison with the results of neutron activation analysis (NAA), delayed neutron counting (DNC) technique or fluorometric method. It is found that NIF method using SSNTDs is very sensitive for analysis of uranium.
Keywords: Neutron induced fissionography; track detectors; uranium analysis; Black Sea sediments